EPITOPES IDENTIFICATION OF BROADLY NEUTRALIZING MONOCLONAL ANTIBODIES AGAINST Corynebacterium diphtheriae EXOTOXIN - Ya.S. Kulyk; A.A. Siromolot; D.V. Kolybo (Biotechnologia Acta, 2022)
Background. Better and high-potency vaccines against diphtheria are urgently needed to provide broader protection against diverse strains and subtypes. Identification of novel broadly neutralizing epitopes targeted by protective antibodies could aid in such efforts.